Syntheses and Characterization of Coordination Compounds of Monobasic Bidentate OS Donor Polystyrene-Anchored Azetidinone - Kumar, Dinesh; Kumar, Amit; Dass, Durga; Kumar Gupta, Praveen (Asian Journal of Chemistry, 2010)
The nucleophillic addition reaction followed by the elimination of one water molecule between polystyrene 3-formylsalicylate (PSCH2-Fsal) and 2-aminoethanethiol in DMF in presence of ethyl acetate and triethylamine results in the formation of polystyrene N-(2-thiohydroxyethyl)- 2′-hydroxybenzalideneimine-3′-carboxylate (PSCH2-LH2). A dioxane suspension of PSCH2-LH2 reacts with chloroacetyl chloride in presence of triethylamine to form polystyrene N-(2-thiohydroxyethyl)-4-(3'- carboxy-2'-hydroxyphenyl)azetidin-2-one, PSCH2-L'H2 (I). A DMF suspension of I reacts with appropriate metal ions and forms [PSCH2- L'HM(OAc)·DMF] [where M = Cu(II), Co(II), Zn(II), Cd(II), UO2(VI)], [PSCH2-L'HM'(OAc)·3DMF] [here M' = Ni(II), Mn(II)], [PSCH2-L'HMoO2- (acac)] and [PSCH2-L'HZr(OH)3· 2DMF]. A square planar structure to [PSCH2-L'HM(OAc)·DMF] [here M = Cu(II), Co(II)]; a tetrahedral structure to [PSCH2-L'HM'(OAc)· DMF] [here M' = Zn(II), Cd(II)]; an octahedral structure to [PSCH2-L'HM'(OAc)·3DMF] [here M' = Ni(II), Mn(II)] and [PSCH2-L'HM(OAc)·DMF] [here M = MoO2(VI), UO2(VI)] and a pentagonal bipyramidal structure to [PSCH2-L'HZr(OH)3·2DMF] have been suggested. The compounds of Cu(II), Co(II), Ni(II) and Mn(II) are paramagnetic and magnetically dilute, while those of others are diamagnetic. This is the first report on the polystyrene-anchored coordination compounds containing the versatile therapeutic azetidinone moiety.